Presepsin v diagnostice sepse - Káňová, Marcela; Dobiáš, Radim; Liszková, Kateřina; Frelich, Michal; Ječmínková, Renáta; Kula, Roman (Vnitrni lekarstvi, 2019)
Sepsis remains one of the most common causes of death worldwide. It is caused by a complex of inadequate host responses to infection. It is also often difficult to distinguish sepsis from a non-infectious cause of systemic inflammatory response syndrome. Early identification of an infectious origin may dramatically help to improve the outcome and reduce mortality. That is the main reason why clinicians need fast, reliable and specific biomarkers for recognition of sepsis. Presepsin (sCD-14ST) is one of promising biomarkers, the level of which increases in response to a microbial infection in the host. As a glycoprotein expressed in the membranes of monocytes and macrophages, CD14 (cluster of differentiation 14) serves especially as a co-receptor of the lipopolysaccharide-lipopolysaccharide binding protein complexes, and activates the inflammatory cascade. Consequently, during the inflammatory reaction, sCD14-ST, known as presepsin, is cleaved away from plasma. The objective of this article is to determine the diagnostic value of presepsin in the diagnostics of sepsis, assessing its severity, and monitoring the effectiveness of therapeutic interventions, and to establish the prognostic value of this biomarker.
Keywords: Prognosis; Biomarkers; biologické markery; Peptide Fragments; diagnostics; Sepsis; biomarkers; sepsis; lidé; lipopolysacharidové receptory; sepse; prognóza; peptidové fragmenty; presepsin; Humans; Lipopolysaccharide Receptors